Relationship between job satisfaction and work engagement in Chinese kindergarten teachers: Vocational delay of gratification as a mediator - Zang, Lingling; Feng, Yuanchun (Frontiers in Psychology, 2023)
Job satisfaction as a positive job-related emotional state affects teachers’ work engagement. This study explored the relationship between job satisfaction and work engagement in kindergarten teachers and the mediating role of vocational delay of gratification. Six hundred and eleven kindergarten teachers from China were surveyed with the Job Satisfaction Scale, Work Engagement Scale, and Vocational Delay of Gratification Scale. Results showed that kindergarten teachers’ job satisfaction and vocational delay of gratification were positively correlated with work engagement, and vocational delay of gratification played a mediating role between job satisfaction and work engagement. Results of the relationship among job satisfaction, vocational delay of gratification, and work engagement were discussed considering the background of Chinese culture.